A compact dual bevel planar monopole antenna with lumped element for ultra high frequency/very high frequency application - Jusoh, Muzammil (2012)
A novel small size planar monopole antenna operating from 0.1 to 1100 MHz is proposed. A planar monopole antenna constructed with 148 mm x 64 mm of radiating element and 80 mm square of ground plane is suitable for cognitive radio (CR) applications where it can cover a very high frequency and a partial of ultra high frequency (UHF) band for spectrum sensing. The proposed monopole antenna is designed by combining a beveling technique and resistor lumped element loading by employing FR4 substrate for low-cost intention. The integration of the resistor with double bevel contributes to the behavior of an inductor as more current are excited to the ground eventually making the radiating element becomes more magnetic. Furthermore, it is found that 50 degrees of dual bevel angle give optimization results for the impedance bandwidth of the antenna. As a result, the low frequency has shifted to the left and enhanced the antenna's impedance bandwidth significantly from 2.2:1 (103%) to 11:1 (200%). The proposed antenna is also extensively proficient in producing divisive radiation patterns with vertical polarization at four different frequencies; 200, 500, 800, and 1000 MHz. The presented antenna performances clarify the potential of the approach between simulation and the measurement results. Instead of CR, the proposed antenna has attractive potentials to be used for GSM, broadcasting, UHF radio frequency identification (RFID) and radio astronomy applications in the future.